TRAINING SESSIONS SPACING OUT SO AS TO DEVELOP POWER ON SPRINT RUNNERS (GYMNASIUM, 2009)
The improvement of force-speed traits development methodology has been achieved based both onhighest volume and on enhancement of all the performed exercises. Force-speed exercises have beenenhanced by raising hurdles’ height, by increasing the bending angle of the gradient and the patches onwhich jumps have been performed, while the working volume has been adjusted to the age’s needs andabilities, as well as to the contest test specificity.Within the rates proposed by us, there can be found the following classes of means of technical andforce-speed traits development: specific power exercises with weights, dynamic force exercises, force-speedexercises using hurdles and exercises to coordinate movements by muscles groups.Plyometrics exercises over fences that we have used contribute in developing the start power.Concentric and eccentric contractions contribute in the reactive power development. Within the powerdevelopment program we have insisted on the quick and powerful application of force on the ground, havingas purpose the recording of a maximum of motility units at the highest contraction speed.